Development of high reusability trifunctional polyethersulfones microspheres for the removal of methyl orange. (February 2023) - Tan, Wei Yang; Shuit, Siew Hoong; Lim, Steven; Tee, Shiau Foon; Pang, Yean Ling; Ng, Qi Hwa
Abstract: This study focused on the synthesis of trifunctional microspheres with adsorption, degradation, and magnetic responsive properties. Firstly, polyethersulfones (PES) encapsulated poly(diallyldimethyl ammonia) chloride (PDDA) functionalized iron oxide (Fe3 O4 ) microspheres were produced via phase inversion method. The PDDA/Fe3 O4 -PES microspheres were further coated with Fe3 O4 nanoparticles (NPs) on the surface to provide the degradation ability to the formed c-PDDA/Fe3 O4 -PES microspheres. Characterization results such as FTIR analysis confirmed the coating of PDDA on Fe3 O4 NPs, while the TGA analysis proved the excellent thermal stability of microspheres after the incorporation of PDDA/Fe3 O4 NPs. BET specific surface area of microspheres was measured at 13.90 m 2 /g. Besides, the pH drift method confirmed the presence of positive charge on microspheres surface, which is important for the removal of anionic pollutants. Moreover, porous structure of microspheres was also observed under SEM. Formulation study was also carried out to investigate the suitable concentration for the synthesis of microspheres, including the concentration of PES polymer (1–20 wt%), the loading of PDDA/Fe3 O4 NPs (1–5 wt%), and the concentration of polyethylene glycol (PEG) (1–20 wt%). The microspheres synthesized from different formulations were subjected to the batch removal of methyl orange (MO). Results showed that a 72.53 % removal of MO can be obtained under the following microspheres synthesis formulations: 10wt% of PES polymer, 2 wt% of PDDA/Fe3 O4 NPs, and 5 wt% of PEG polymer. Lastly, the c-PDDA/Fe3 O4 -PES microspheres also demonstrated an excellent reusability as compared to pure PES microspheres. The c-PDDA/Fe3 O4 -PES microspheres could be reused up to 5 cycles without the need of regeneration while still maintaining high MO removal efficiency. Graphical abstract: Unlabelled Image Highlights: Trifunctional microspheres with adsorption, degradation, and magnetic responsive properties Feasibility of trifunctional microspheres in the removal of methyl orange High reusability microspheres without the need of regeneration